2015
DOI: 10.1007/s12274-014-0698-2
|View full text |Cite
|
Sign up to set email alerts
|

An indicator-guided photo-controlled drug delivery system based on mesoporous silica/gold nanocomposites

Abstract: A mesoporous silica/gold (MSN/Au) nanocomposite was designed for photocontrolled drug delivery targeted specifically at tumor cells. The MSN/Au nanocomposite was composed of MSN-based drug carriers and gold nanoparticle (AuNP)-based indicators. While the MSN-based drug carrier was a mesoporous silica nanoparticle immobilized with photo-switchable azobenzene (Azo) moieties, the AuNP-based indicator was a fluorescence-quenched AuNP modified with a matrix metalloproteinase (MMP) substrate and poly(ethylene glycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…Among numerous types of nano‐DDSs, nanoparticles with mesoporous structures, for which mesoporous silica nanoparticles (MSNs) are a typical example, have been extensively explored owing to their unique porous structure and large surface area to enable efficient loading of different types of therapeutic or imaging molecules . In particular, MSN‐based nano‐DDSs have shown great promises in the delivery of different types of therapeutics (e.g., chemotherapy, gene therapy, and photodynamic therapy) as demonstrated in numerous preclinical animal experiments . However, as far as chemoradiotherapy is concerned, MSNs are used only as carriers for chemotherapeutic agents, and themselves have no significant sensitizing effect to radiotherapy on account of their weak X‐ray absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Among numerous types of nano‐DDSs, nanoparticles with mesoporous structures, for which mesoporous silica nanoparticles (MSNs) are a typical example, have been extensively explored owing to their unique porous structure and large surface area to enable efficient loading of different types of therapeutic or imaging molecules . In particular, MSN‐based nano‐DDSs have shown great promises in the delivery of different types of therapeutics (e.g., chemotherapy, gene therapy, and photodynamic therapy) as demonstrated in numerous preclinical animal experiments . However, as far as chemoradiotherapy is concerned, MSNs are used only as carriers for chemotherapeutic agents, and themselves have no significant sensitizing effect to radiotherapy on account of their weak X‐ray absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, results indicated the feasibility of MMP‐9 mediated drug release in an advanced mouse model and human lung tissue using the new experimental setup of ex vivo 3D lung tissue cultures. Besides, to precisely control the release timing, location, and dosage of therapeutic agents in a photo‐controlled triggered DDS, our group reported that gold nanoparticles (AuNPs) functionalized with carboxyfluorescein‐conjugated MMP‐2 sensitive peptides (FAM‐GGPLGLAC) were used as the tumor indicator for the photo‐switchable azobenzene (Azo)‐functionalized MSN . As shown in Figure , once it arrived at tumor site, the cleaved GGPLGLAC peptide led to the recovery of green fluorescence (FAM) and could be used to guide the subsequent ultraviolet (UV)‐irradiation, which would transform trans‐Azo to cis‐Azo, the MSNs pores would be open and release the entrapped DOX at tumor site.…”
Section: Stimuli‐responsive Peptidesmentioning
confidence: 99%
“…I) Tumor tissue overexpressed MMP‐2; II) specific cleavage of the MMP‐2 substrate peptide, leading to subsequent fluorescence recovery; III) fluorescence‐guided UV light irradiation and DOX release; IV) tumor cells killed by the released DOX. Reproduced with permission . Copyright 2014, Springer.…”
Section: Stimuli‐responsive Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…This arrangement would block pore outlets to prevent the release of the payload, while also allowing the anchoring of targeting elements easily. Similar strategies have been employed successfully, as reported in the literature, through which coating with AuNPs has been performed through electrostatic deposition, cyclodextrin– adamantane supramolecular interactions, acid‐sensitive linkers, or displaceable DNA sequences . Notwithstanding the above disadvantages, all reported models suffer from a low Au to MSNs ratio, which does not ensure efficient capping, as observed from published TEM images.…”
Section: Introductionmentioning
confidence: 99%